Table 1_Adolescent emotional responses to different music arrangements.docx - Yaming Wei (3619427) (2025)
Objective This study aims to investigate adolescents’ positive emotional responses to different music arrangements, focusing on the influence of gender, music preference, and personal musical experience on emotional responses. The hypothesis proposes that gender and musical experience have a significant impact on adolescents’ emotional responses to music. Methods The study recruited 120 adolescents who listened to three different arrangements of the same song. Emotional responses were assessed using the Positive and Negative Affect Schedule (PANAS), alongside physiological measures including electrodermal activity (EDA) and heart rate variability (HRV). Statistical analyses, including analysis of variance (ANOVA) and correlation analysis, were employed to evaluate the effects of gender, music preference, and personal musical experience on emotional responses. Results Female participants showed higher PANAS scores for certain music arrangements. Music education or artistic training had no significant effect. Music preference was negatively correlated with emotional responses, while listening experience had a significant positive impact. Physiologically, the rock version (B) elicited the highest EDA, the classical version (A) showed the highest HRV, and the bossa nova version (C) yielded moderate responses in both measures. Conclusion Gender and personal music preferences play important roles in adolescents’ emotional responses to musical arrangements. These findings hold potential applications in music therapy, education, and psychological health interventions for adolescents.